Performance assessment of security mechanisms for cooperative mobile health applications - Canelo, Fábio Alexandre Afonso (2015)
Mobile health (m-Health) applications aim to deliver healthcare services through mobile applications regardless of time and place. An mHealth application makes use of wireless communications to sustain its health services and often providing a patient-doctor interaction. Therefore, m-Health applications present several challenging issues and constraints, such as, mobile devices battery and storage capacity, broadcast constraints, interferences, disconnections, noises, limited bandwidths, network delays, and of most importance, privacy and security concerns. In a typical m-Health system, information transmitted through wireless channels may contain sensitive information such as patient’s clinic history, patient’s personal diseases information (e.g. infectious disease as HIV - human immunodeficiency virus). Carrying such type of information presents many issues related to its privacy and protection. In this work, a cryptographic solution for m-Health applications under a cooperative environment is proposed in order to approach two common drawbacks in mobile health systems: the data privacy and protection. Two different approaches were proposed: i) DE4MHA that aims to guarantee the best confidentiality, integrity, and authenticity of mhealth systems users data and ii) eC4MHA that also focuses on assuring and guarantying the m-Health application data confidentiality, integrity, and authenticity, although with a different paradigm. While DE4MHA considers a peer-to-peer node message forward, with encryption/decryption tasks on each node, eC4MHA focuses on simply encrypting data at the requester node and decrypting it when it reaches the Web service. It relays information through cooperative mobile nodes, giving them the only strictly required information, in order to be able to forward a request, until it reaches the Web service responsible to manage the request, and possibly answer to that same request. In this sense, the referred solutions aim any mobile health application with cooperation mechanism embedded. For test purposes a specific mobile health application, namely SapoFit, was used. Cryptographic mechanisms were created and integrated in SapoFit application with built in cooperation mechanisms. A performance evaluation of both approaches in a real scenario with different mobile devices is performed and presented in this work. A comparison with the performance evaluations of both solutions is also presented.